PENERAPAN PEMBELAJARAN DIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS III SD/MI - Rosyidatul Kholidah, Dwi; Anwar Badruttamam, Choerul (Jurnal keilmuan dan Kependidikan dasar, 2023)
This research was designed with the aim of improving student learning achievement using the differentiation method for grade II elementary school students with science material. This type of research is Classroom Action Research (PTK), where the teacher is the implementer of the learning while the researcher is the observer.The use of differentiated instruction can be applied at all school levels, including elementary school (SD). This time, a learning approach was used: Classroom Action Study (PTK) to assess student performance in science and social studies (IPAS). The objectives of this action research are: (a) to evaluate the effectiveness of implementing differentiation learning in improving academic outcomes, (b) the impact of implementing differentiation learning on students' academic OUTCOMES from 2nd year SD Negeri Blimbing 3, Lamongan , to determine. Regency. The analysis results show that the academic performance of students from Cycle I to Cycle III, i.e. H. H., increased significantly.Cycle I (66.68%), Cycle II (77.79%) and Cycle III (88.90%). The conclusion of this research is that the use of differentiated learning effectively increases the academic results and learning outcomes of SD Negeri Blimbing 3 Grade 2 students. This learning model can be used as an effective alternative to science learning at school level. Basic level/MI.